2000
DOI: 10.1046/j.1440-1681.2000.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

Area Postrema And Sympathetic Nervous System Effects Of Vasopressin And Angiotensin II

Abstract: 1. Precise control over the cardiovascular system requires the integration of both neural and humoral signals related to blood volume and blood pressure. Humoral signals interact with neural systems, modulating their control over the efferent mechanisms that ultimately determine the level of pressure and volume. 2. Peptide hormones such as angiotensin (Ang)II and arginine vasopressin (AVP) act through circumventricular organs (CVO) to influence cardiovascular regulation. 3. The area postrema (AP), a CVO in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…We conclude that the effect of AT 1 receptor antagonists in the expression of TH mRNA in the locus coeruleus may not be direct. Indirect effects may include inhibition of brain stem AT 1 receptors located in the nucleus of the solitary tract and the area postrema, as reported here, along with the blood pressure decrease and changes in the baroreflex that follow AT 1 receptor antagonism (Hasser et al 2000) and inhibition of the CRH mediation of the stress-induced stimulation of neuronal activity in this area (Porter 2000;Makino et al 2002;Zeng et al 2003).…”
Section: Effects Of Candesartan Treatment and Cold-restraint Stress Omentioning
confidence: 61%
“…We conclude that the effect of AT 1 receptor antagonists in the expression of TH mRNA in the locus coeruleus may not be direct. Indirect effects may include inhibition of brain stem AT 1 receptors located in the nucleus of the solitary tract and the area postrema, as reported here, along with the blood pressure decrease and changes in the baroreflex that follow AT 1 receptor antagonism (Hasser et al 2000) and inhibition of the CRH mediation of the stress-induced stimulation of neuronal activity in this area (Porter 2000;Makino et al 2002;Zeng et al 2003).…”
Section: Effects Of Candesartan Treatment and Cold-restraint Stress Omentioning
confidence: 61%
“…A significant body of work has established that the circulating hormone arginine vasopressin acts directly on AP neurons, to inhibit sympathetic output and shift the baroreceptor reflex setpoint to lower arterial pressure (26,59; for a review, see also Ref. 25). Intriguingly, ghrelin is also reported to have cardiovascular effects by modulating baroreflex sensitivity.…”
Section: Examples Of Results From Nonresponding Neurons (A) Hyperpolmentioning
confidence: 99%
“…Past research has demonstrated that elevated levels of ANG II can act within the central nervous system to stimulate sympathetic outflow (27,34,42) and may attenuate baroreflex inhibition of sympathetic nerve activity (49). However, other research has shown that ANG II either had no effect (24) or attenuated (43) baroreflex-mediated sympathetic responses to hypotension.…”
Section: Discussionmentioning
confidence: 99%